Synthesis and Ameliorating the Morphological, Microstructure and Optical Features of PMMA-PEG/BaTiO3 Nanostructures for Flexible Photonics and Optics Devices - Hashim, Ahmed; Ahmed, Ghaith; Al Maimuri, Najah M. L.; Ibrahim, Hamed; Hadi, Aseel; Uthra, Dinesh (Trends in Sciences, 2024)
The polymer nanocomposites are important materials for many optical and electronic applications. This research aims to fabricate of barium titanate (BaTiO3) NPs doped polyethylene glycol (PEG)-polymethyl methacrylate (PMMA) to apply in various photonics and optical approaches. The (PEG-PMMA/BaTiO3) films were coursed using the casting method. The microstructure and optical characteristics of (PEG-PMMA/BaTiO3) films were investigated. The optical features results showed when the BaTiO3 NPs content reached 5 wt.%, the transmission(T) was reduced whereas the absorption(A) was augmented. The energy gap (Eg) of the (PEG-PMMA) blend decreased from 2.5 to 1.9 eV with increasing BaTiO3 NPs concentration to reach of 5 wt.% making the (PEG-PMMA/BaTiO3) nanostructures are suitable for optical and optoelectronic nanodevices. The refractive index, real and imaginary dielectric constants, absorption coefficient, optical conductivity and extinction coefficient were improved with increasing BaTiO3 NPs concentration. Finally, the obtained findings indicated that the (PEG-PMMA/BaTiO3) nanostructures might be employed in a range of optical applications. HIGHLIGHTS Preparation of (PEG-PMMA/BaTiO3) films to apply in various photonics and optical approaches. The microstructure and optical characteristics of (PEG-PMMA/BaTiO3) films were investigated. The energy gap (Eg) of the (PEG-PMMA) blend decreased from 2.5 to 1.9 eV with increasing BaTiO3 NPs concentration to reach of 5 wt.% making the (PEG-PMMA/BaTiO3) nanostructures are suitable for optical and optoelectronic nanodevices. The optical parameters were improved with increasing BaTiO3 NPs concentration which are welcomed in a range of optical applications. GRAPHICAL ABSTRACT